This dark descent - Josephson, Kalyn (Roaring Brook Press, 2023)
Mikira, a seventeen-year-old daughter of a famous horse breeder, takes part in a magical horserace to save her family, and enlists the help of Arielle, a talented, black-market enchanter, and Damien, a young lord involved in a succession battle, who both have their own motives for helping her.